1995
DOI: 10.1016/0269-7491(95)91435-n
|View full text |Cite
|
Sign up to set email alerts
|

Reduced breeding success of Cormorants (Phalacrocorax carbo sinensis) in relation to persistent organochlorine pollution of aquatic habitats in The Netherlands

Abstract: Reduced breeding success of cormorants (Phalacrocorax carbo sinensis) in relation to persistent organochlorine pollution of aquatic habitats in the netherlands. Dirksen, S.; Boudewijn, T.J.; Slager, L.K.; Mes, R.G.; van Schaick, M.J.M.; de Voogt, W.P. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
2
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 43 publications
3
44
2
1
Order By: Relevance
“…Whereas the familiar phenomenon of eggshell thinning and subsequent reproductive failure (Hickey and Anderson 1968) was generally attributed to dysfunction of the eggshell gland in mature females, subsequent mortality or reduced performance of many of those individuals that did not succumb to eggshell thinning suggests that toxicity of maternally derived contaminants was an additional mechanism by which reproductive success was reduced (Dirksen et al 1995, Fry 1995. Effects on offspring ranged from embryonic and juvenile mortality to morphological malformations that may hinder feeding (Fox et al 1991, Tillitt et al 1992.…”
Section: Physiological and Reproductive Traits And Risks Of Contaminamentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the familiar phenomenon of eggshell thinning and subsequent reproductive failure (Hickey and Anderson 1968) was generally attributed to dysfunction of the eggshell gland in mature females, subsequent mortality or reduced performance of many of those individuals that did not succumb to eggshell thinning suggests that toxicity of maternally derived contaminants was an additional mechanism by which reproductive success was reduced (Dirksen et al 1995, Fry 1995. Effects on offspring ranged from embryonic and juvenile mortality to morphological malformations that may hinder feeding (Fox et al 1991, Tillitt et al 1992.…”
Section: Physiological and Reproductive Traits And Risks Of Contaminamentioning
confidence: 99%
“…Maternal transfer of contaminants to offspring has been well documented in long-lived species, including mammals (Aguilar and Borrell 1994, Henriksen et al 2001, Skaare et al 2002, Beckmen et al 2003, Schecter et al 2003, Hickie et al 2007), birds (Dirksen et al 1995, Ewins et al 1999, Hebert et al 2000, and reptiles (Bishop et al 1994, Rauschenberger et al 2004). Transfer of metals (such as selenium and mercury) has been observed in some species (e.g., Roe et al 2004), but most attention has focused on persistent synthetic compounds, particularly halogenated compounds such as PCBs and some pesticides.…”
Section: Physiological and Reproductive Traits And Risks Of Contaminamentioning
confidence: 99%
“…middle sized fish predominantly in the families cyprynidae and percidae, and to the ban on agricultural use of DDT-containing pesticides. The above compound bioaccumulated along the trophic chain and led to marked thinning of eggshells resulting in decreased hatching success in birds (Dirksen et al, 1995). The great cormorant is a true piscivorous bird that feeds on numerous species of fish and thus is exposed to a variety of parasites that use fish as intermediate hosts.…”
Section: Introductionmentioning
confidence: 99%
“…The PCB females and males produced fewer fledglings than did control pairs, indicating that PCB effects occur through both sexes independently. Declines in fledging success have been observed in wild tree swallows (McCarty and Secord 1999), cormorants Dirksen et al 1995), and the captive kestrels directly exposed to dietary PCBs (Fernie et al 2000a). As seen in wild cormorants (Custer et al 1999), nestling kestrels died either at or within the first 3 days of hatching in kestrel pairs experiencing either in ovo or dietary PCB exposure (Fernie et al 2000a).…”
Section: Discussionmentioning
confidence: 96%
“…They also bioaccumulate through the food web (Hoffman et al 1996) and are potential endocrine-modulating substances (Koval et al 1987). Reproduction of wild passerines (McCarty and Secord 1999;Bishop et al 1999), raptorial (Kozie and Anderson 1991;Bowerman et al 1994;Giesy et al 1995;Hoffman et al 1998), and piscivorous Dirksen et al 1995;Custer et al 1999) birds has been altered by exposure to multiple contaminants, including PCBs. Most of these studies of wild birds have shown that there are contaminant effects at all levels, from compromised fertility and reduced hatching success of fertile eggs to diminished survival of young birds prior to or after fledging from the nest.…”
mentioning
confidence: 99%